Isolation, molecular identification, and genomic analysis of Mangrovibacter phragmitis strain ASIOC01 from activated sludge harboring the bioremediation prowess of glycerol and organic pollutants in high-salinity - Chin, Hong Soon; Ravi Varadharajulu, Narendrakumar; Lin, Zhi-Han; Chen, Wen-Yu; Zhang, Zong-Han; Arumugam, Sankar; Lai, Ching-Yen; Yu, Steve S.-F. (Frontiers in Microbiology, 2024)
The physiological and genotypic characteristics of Mangrovibacters (MGBs) remain largely unexplored, including their distribution and abundance within ecosystems. M. phragmitis (MPH) ASIOC01 was successfully isolated from activated sludge (AS), which was pre-enriched by adding 1,3-dichloro-2-propanol and 3-chloro-1,2-propanediol as carbon sources. The new isolate, MPH ASIOC01, exhibited resilience in a medium containing sodium chloride concentration up to 11% (with optimal growth observed at 3%) and effectively utilizing glycerol as their sole carbon source.However, species delimitation of MGBs remains challenging due to high 16S rRNA sequence similarity (greater than 99% ANI) among different MGBs. In contrast, among the housekeeping gene discrepancies, the tryptophan synthase beta chain gene can serve as a robust marker for fast species delimitation among MGBs. Furthermore, the complete genome of MPH ASIOC01 was fully sequenced and circlized as a single contig using the PacBio HiFi sequencing method.Comparative genomics revealed genes potentially associated with various phenotypic features of MGBs, such as nitrogen-fixing, phosphate-solubilizing, cellulose-digesting, Cr-reducing, and salt tolerance. Computational analysis suggested that MPH ASIOC01 may have undergone horizontal gene transfer events, possibly contributing unique traits like antibiotic resistance. Finally, our findings also disclosed that the introduction of MPH ASIOC01 into AS can assist in the remediation of wastewater chemical oxygen demand, which was evaluated using gas chromatograph-mass spectrometry. To the best of our knowledge, this study offers the most comprehensive understanding of the phenotypic and genotypic features of MGBs to date.